Monitoring Techniques of Bone Fracture Healing Using External Fixators - Jasińska-Choromańska, D.; Sadzyński, I. (Engineering Transactions, 2015)
Long bone fractures can be healed using external fixators – devices that stiffly fix the fractured fragments, attached to the bone by pins parallel to the bone frame. This method enables to benefit both from healing and diagnostics of fracture during osteogenesis. Osteogenesis, traditionally diagnosed using X-rays methods (RTG, densitometry), can also be more precisely determined with mechanical properties like strength and stiffness inside the fracture slot. The treatment of long bone fractures by external fixators offers a unique opportunity to control the healing of the fracture by measuring the compression forces on the frame, that occurs under the load applied to the bone and depends on the mechanical properties of the fracture. The procedure of measurement of the compression force on the frame can be performed using tensometers, what is a cheap and simple method, and can be performed by the patient at home. The measurement of osteogenesis gives a possibility of more precise diagnostics of the fracture. It can also be combined with computer techniques like artificial intelligence. The paper presents one of the methods of monitoring the bone fracture healing.